Retrospective reproduction analysis in female reindeer (Rangifer tarandus) - Heggberget, Thrine Moen (Rangifer, 2002)
Retrospective reproduction analysis has proven a useful study method for many mammal species, but the method has not been used as much in reindeer and caribou studies as it deserves.